2000
DOI: 10.1073/pnas.200366897
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric aerosols as prebiotic chemical reactors

Abstract: Aerosol particles in the atmosphere have recently been found to contain a large number of chemical elements and a high content of organic material. The latter property is explicable by an inverted micelle model. The aerosol sizes with significant atmospheric lifetimes are the same as those of single-celled organisms, and they are predicted by the interplay of aerodynamic drag, surface tension, and gravity. We propose that large populations of such aerosols could have afforded an environment, by means of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
253
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(256 citation statements)
references
References 29 publications
2
253
0
1
Order By: Relevance
“…Figure 2 demonstrates that after enough time has elapsed, the fatty acid peaks have decreased by large fractions and chlorine peaks (m/z = 35 and 37) have increased by large fractions, demonstrating that the fatty acids are on the exterior of a sea salt core. This observation confirms the hypothesis of Ellison et al, (1999) that such would be the structure of marine aerosols, and which led to the connection to the origin of life (Dobson et al, 2000). In the present biotic atmosphere, these fatty acids come from the decay of lipids (Sicre et al, 1990); we examine the supply of fatty acid monomers in the prebiotic era in Section 3 below.…”
Section: Recent Observational Evidencesupporting
confidence: 74%
See 2 more Smart Citations
“…Figure 2 demonstrates that after enough time has elapsed, the fatty acid peaks have decreased by large fractions and chlorine peaks (m/z = 35 and 37) have increased by large fractions, demonstrating that the fatty acids are on the exterior of a sea salt core. This observation confirms the hypothesis of Ellison et al, (1999) that such would be the structure of marine aerosols, and which led to the connection to the origin of life (Dobson et al, 2000). In the present biotic atmosphere, these fatty acids come from the decay of lipids (Sicre et al, 1990); we examine the supply of fatty acid monomers in the prebiotic era in Section 3 below.…”
Section: Recent Observational Evidencesupporting
confidence: 74%
“…The idea itself is now buttressed by observations in the contemporary atmosphere (Murphy et al, 1998;Tervahattu et al, 2002aTervahattu et al, , 2002b, and can be traced back through earlier suggestions by Goldacre (1958), Shah (1970) and Lerman (1986Lerman ( , 1992Lerman ( , 1994Lerman ( , 1996. Dobson et al (2000) gave an equation (Kasten 1968) expressing how the balance between gravitation and aerodynamic drag determines the size of aerosol particles having an appreciable residence time in the atmosphere, and Donaldson et al (2001) showed thermodynamically how the free energetics of the collapse of an exterior film of amphiphilic molecules on an aerosol could lead to fission, a process not possible for a homogeneous uncoated liquid aerosol. The fission must be asymmetric; for a prebiotic Earth atmosphere with one bar surface pressure, the larger daughter particle is bacterially-sized while the smaller one is virally-sized .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Atmospheric aerosols, however, are known to experience a wide range of pH values throughout their atmospheric lifetime, and can reach acidic pH values at which this chemistry will become dominant (56). These aerosol particles have the added advantage of concentrating the reactant species through selective evaporation of water, resulting in high concentrations of reactant monomers (57)(58)(59)(60)(61). Therefore, although this chemistry is unlikely to be an important contributor to bulk ocean chemistry, it will be important in acidic aqueous atmospheric aerosols.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…The air-water interface (atmospheric aerosols in particular) has previously been proposed to be important in prebiotic chemistry (11)(12)(13)(14) because it provides a unique environment for chemistry through its ability to concentrate and align biochemical precursors and to alter the state of ionization of surface species (15)(16)(17)(18)(19). Contemporary marine aerosols have been found to contain the amino acid precursors necessary for peptide bond chemistry (20), enabling the possibility for their use in such reactions.…”
mentioning
confidence: 99%